TI_GERICHTE 11.2021.93 vom 9. März 2023 , Responsabilità del proprietario: lancio di oggetti su un fondo vicino - TI Tribunale d'appello (2023)
Responsabilità del proprietario: lancio di oggetti su un fondo vicino